Monitoring costs, credit constraints and entrepreneurship - Sanjay Banerji; Rajesh S. N. Raj; Kunal Sen (Institute for the Study of Labor (IZA), 2012)
The vast majority of firms in developing economies are micro and small enterprises owned by families whose members also provide the labour to the units. Often, they fail to grow in size even with the relaxation of credit constraints. In this paper, we show that frictions in the labour market leading to monitoring costs tend to reduce the growth of the firm via two channels: (1) it forces the entrepreneur to devote more time on monitoring hired labour from outside family which curtails her time on productive activities leading to failures of firm's projects. (2) The need to pay a premium wage over the market rate in order to incentivize workers makes it costlier for the firm to expand in size via hiring outside labour. In this framework, we show that possibility of an inverted U- shaped relationship between the credit supply and the size of the firm, measured by hiring of non family labour, indicating frictions in the labour market may outweigh the effects of the easing of borrowing constraints of the firm. We then use a unique data-set comprising large nationally representative surveys of small and micro-enterprises in Indian manufacturing and find support for the existence of such a non-monotonic relationship attributed to both frictions in the credit and labour markets.
urn:nbn:de:101:1-201305226074
Keywords: D22; G10; O16; 330; entrepreneurship; monitoring costs; credit constraint; household enterprises; India; Unternehmer; Familienunternehmen; KMU; Verschuldungsrestriktion; Personalkontrolle; Kosten; Unternehmenswachstum; Theorie; Indien